Isco Foundation Children's Educational Support Implementation Program In The Cipinang Region - Maria Josefin Barus; Ety Rahayu (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Education is an important part that must be owned by many people in order to improve the standard of living. In an effort to overcome this problem, the ISCO Foundation's Children Educational Support (CES) program is present in several regions in Indonesia, namely Medan, Surabaya and Jakarta. This study aims to evaluate the implementation of ISCO foundation’s Children Educational Support program in the Cipinang assisted area, East Jakarta. This study used a qualitative approach by conducting in-depth interviews and direct observations of the participants of the CES program. The research results show that the program implementation has been running in accordance with the ISCO Foundation Program theory. The ISCO Foundation plays an important role in improving education for children by providing support in education at school and outside school. The ISCO program helps poor children to attain education up to high school/vocational school level and some are even able to complete higher education. This research can be a basis for developing more effective policies and strategies in improving education in Jakarta and other regions in Indonesia.